The Effectiveness of Using Best Friend Song by Rex Orange County in Enhancing Second Grade Students Asking and Giving Opinion - Herman, Alfan Alfian; Gumelar, Wahyu Satya; Hidayat, Hamdan (Journal of Educational Sciences, 2025)
This study aims to examine the effectiveness of using the song "Best Friend" by Rex Orange County in improving students' speaking skills, particularly in asking and giving opinions. The method used is a quantitative approach with a one-group pretest-posttest type quasi-experimental design. The research sample consisted of 24 eleventh-grade students from SMA Istiqomah Bandung, selected through purposive sampling technique. The research instrument in the form of an oral test was administered before and after the treatment of learning with song media. The results of the data analysis show a significant increase in the average student scores, from 64.17 on the pretest to 85.04 on the posttest. The paired sample t-test produced a significance value of p < 0.001, indicating that the use of the song was effective in improving students' speaking abilities in the context of asking and giving opinions. Thus, popular songs can be used as an enjoyable and contextual alternative learning medium to enhance students' oral competence in English language learning at the secondary school level.